The impact of maternal obesity on maternal and fetal outcome - A., Esther Kamalarani; ., Ramyajothi; S., Ramalakshmi (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2019)
Background: Obesity continues to be a global health concern. Although the increasing obesity rates in developed countries has slowed down in the past 10 years, obesity rates in developing countries continue to increase, as much as three times in some developing countries over the past 30 years. The aim of the study was to determine the adverse effects of obesity in pregnancy and maternal and fetal outcome. Methods: In all patients, a detailed history was taken and examinations and investigations were carried out. Based on BMI (body mass index), patients were divided into 2 groups. Group 1 = patients with BMI >30 kg/m2 and Group 2 = patients with BMI <30 kg /m2. Results: In our study, comparing pregnant mothers with BMI >30 kg/m2 and normal BMI, authors found that the prevalence of maternal and fetal complications was higher in the obese group. Prevalence of antenatal complications like gestational hypertension, preeclampsia, imminent eclampsia and gestational diabetes mellitus requiring control with insulin was higher in obese women. Conclusions: Obesity is associated with increased adverse effects on pregnancy and its outcome.